BIOGRAPHICAL AND RELATIONAL PROFESSIONAL IDENTITY OF THE NURSE MANAGER - Silva, Thaís Araújo da; Freitas, Genival Fernandes de (Cogitare Enfermagem, 2023)
Objective: to know and understand the perceptions and meanings attributed to the biographical and relational identity of being a nurse by the social group that acted as director of the Department and Division of Nursing of the University Hospital of the University of São Paulo. Method: social-historical study with a qualitative approach. Data collection occurred between March and November 2017. The theory of Claude Dubar was used as a theoretical reference. Eleven interviews were conducted, which were analyzed by the technique of Discourse Analysis. Results: two categories emerged. The first highlighted the articulation process, the practice of care, and the Teaching-Assistance Integration program, and addressed aspects related to power and the model-reference. The second listed the role of the teacher/manager and emphasized issues related to recognition and respect. Conclusion: this study may contribute to the recognition and visibility of the Nursing area, especially in the field of assistance, management, and teaching.